FAKTOR YANG BERHUBUNGAN DENGAN PEMBERIAN ASI EKSKLUSIF DI WILAYAH KERJA PUSKESMAS TAMALATE KOTA MAKASSAR - Rosdiana Syakur; Hardi Kalmi; Maryono Dassi; Erni Erni (Program Studi Ilmu Kesehatan Masyarakat, Fakultas Kesehatan Masyarakat, Universitas Indonesia Timur, 2020)
Background : Breastfeeding (ASI) to the baby is a natural way to give food for the baby. Excclusive breastfeeding is providing only breast milk without giving other food and drinks for the baby from the birth until the age of 6 months, except drugs and vitamins. It is unsignificantly that after exlusive breastfeeding, giving breast milk is stopped, but the baby is still given breast milk until he is in the age of 2 years. The Method : This research was conducted at the tamalate health center, tamalate district, Makassar city, the research method used was the analytic survey method by supporting the cross sectional design, the research used 75 population . the number of sample was 63 sample. The sampling technique used was the purposive sampling. Data were analyzed by using the univariate, bivariate analysis supporting chi-square test.The Research Result : Based on bivariate analysis, the research result indicates that there is the relationship between knowledge and exclusive breastfeeding with p = 0.010, Occupation p = 0,23, Age p = 0,010, Family Support p = 0,031 Conclusion : It is suggested that the mother must pay more attention to give the exclusive breast milk, to meet more the nutritional needs and to maintain the immune system for the baby in order to advoid various diseases attacking.